Clinical researchCyclosporine A – treated nephrotic children show impaired vasodilatation but no autonomic neuropathy - Czupryniak, Aneta; Kałużyńska, Anna; Półtorak-Krawczyk, Anna; Ostrowski, Bartosz; Więcek, Bogusław; Tkaczyk, Marcin (Archives of Medical Science, 2010)
Introduction: The aim of the study was to determine the effect of long-term cyclosporine A (CsA) treatment in children with idiopathic nephrotic syndrome on autonomic nerve function and peripheral blood flow assessed with thermography. Material and methods: The study group consisted of 19 nephrotic children treated with cyclosporine A compared to 16 healthy children. The assessment of blood flow was made based on the results of thermographic measurements during the cold stress test by an infrared radiation registering camera. Ewing’s battery of non-invasive tests was used to assess autonomic function. Results: The study showed diminished temperature increase after the cooling test in children with nephrotic syndrome treated with CsA. Sympathetic activity test results were comparable to healthy children. Conclusions: It may be hypothesized that cyclosporine A administered even in low doses induces small vessel dysfunction measured by the thermographic method. This effect seems to be independent of sympathetic nervous system involvement, which was absent in cyclosporine A treated nephrotic children.